The Risk Analysis of Malnutrition by Tooth Loosing Among Elderly - Febrian; Shindy Ollivia (Denta Journal Kedokteran Gigi, 2020)
Introduction: Tooth loss occurs mostly in the elderly, especially loss of occlusal support can cause disruption of the mastication process and the swallowing of food, so the chewing function is reduced and causes the elderly to prefer soft foods and foods that are easy to chew. The lack of fulfillment of all nutrients needed by the body as the risk of malnutrition in the elderly increases.Purpose: To evaluate the analysis of tooth loss in the elderly with mal-nutrition based on Mini Nutritional Assessment in Social House Tresna Werdha Kasih Sayang Ibu, Batusangkar. Materials and Methods: Cross-Sectional approach. The total number of the sample was 46 elderly. The Eichner index measured the tooth loss, besides the MNA questionnaire estimated the risk of malnutrition. Data analysis was done using Chi-square Results: 76.1% of the elderly have tooth loss (all of the occlusal support) and 69.7% of the elderly at risk of malnutrition. 85.7% of the elderly have tooth loss (all of the occlusal support) with risk malnutrition. The statistical result analyzed by using Chi-square obtained p-value <0.005. Conclusion: There is a risk of malnutrition in the elderly who experience tooth loss